2015
DOI: 10.1111/ajo.12410
|View full text |Cite
|
Sign up to set email alerts
|

The impact of altering filling pressures in diagnostic outpatient hysteroscopy on the procedure completion rates and associated pain: a randomised double‐blind controlled trial

Abstract: Uterine filling pressure of 50 mm Hg was associated with better visualisation than 30 mm Hg and lower pain scores than that of 80 mmHg with no difference in the proportion of completed procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…The present results are in agreement with a previous randomized trial that included 240 women undergoing diagnostic hysteroscopy and compared uterine filling pressures of 30, 60, and 80 mm Hg. In that study, pain scores increased progressively with increasing pressure, whereas visibility was lowest in the group with a filling pressure of 30 mm Hg.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results are in agreement with a previous randomized trial that included 240 women undergoing diagnostic hysteroscopy and compared uterine filling pressures of 30, 60, and 80 mm Hg. In that study, pain scores increased progressively with increasing pressure, whereas visibility was lowest in the group with a filling pressure of 30 mm Hg.…”
Section: Discussionsupporting
confidence: 93%
“…Operative hysteroscopy was performed as described previously using a vaginoscopic approach. Saline at room temperature was used as the distention medium, with an even pressure maintained by an automated pressurized pump.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many published studies have evaluated the use of different pain‐management strategies. However, view studies investigating optimal intrauterine filling pressure have been performed in outpatient HSC only, and only two studies were randomized trials conducted from a diagnostic HSC perspective . From the published work, we have concluded that there are two reasonable options for evaluating intrauterine filling pressure in outpatient HSC, namely low pressure states (30–50 mmHg) and high‐pressure states (70–100 mmHg).…”
Section: Introductionmentioning
confidence: 99%